1981
DOI: 10.1084/jem.154.2.517
|View full text |Cite
|
Sign up to set email alerts
|

Retroviral gp70 immune complexes in NZB x NZW F2 mice with murine lupus nephritis.

Abstract: NZB x NZW (NZB x W) F1 hybrid mice spontaneously develop a disease most prominently characterized by immune complex glomerulonephritis (GN), which seems to be associated with both antibodies to DNA and to the serum retroviral envelope glycoprotein, gp70. To evaluate the contribution of each of these autoimmune responses to the pathogenesis of the GN, we studied NZB x W F2 mice in which the two responses appeared to segregate relatively independently. Use of this model permitted analysis of possible correlation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 22 publications
0
41
0
Order By: Relevance
“…In fact, non-Yaa and Yaa B6.bcl-2 Tg males displayed neither measurable levels of gp70-anti-gp70 IC ( X 0.1 ? g/ml), implicated in mouse lupus nephritis [24,25] (Table 1). Nevertheless, more than one third of B cells were still derived from BXSB mice.…”
Section: Induction Of Rf By B6bcl-2 Tg B Cells In Bone Marrow Chimermentioning
confidence: 99%
“…In fact, non-Yaa and Yaa B6.bcl-2 Tg males displayed neither measurable levels of gp70-anti-gp70 IC ( X 0.1 ? g/ml), implicated in mouse lupus nephritis [24,25] (Table 1). Nevertheless, more than one third of B cells were still derived from BXSB mice.…”
Section: Induction Of Rf By B6bcl-2 Tg B Cells In Bone Marrow Chimermentioning
confidence: 99%
“…These mice spontaneously develop an autoimmune disease characterized by the production of IgG autoantibodies and the development of a severe immune complex-mediated glomerulonephritis. The major targets of autoantibodies are chromatin constituents (DNA and histones) and the endogenous retroviral glycoproteins, gp70 (1)(2)(3)(4)(5)(6). Both anti-chromatin and anti-gp70 autoantibodies, measured as gp70-anti-gp70 immune complexes (gp70 IC), have been implicated in the development of the progressive lupus nephritis in (NZB ϫ NZW)F 1 mice (5,(7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Genetic Control Of Glycoprotein 70 Autoantigen Production Anmentioning
confidence: 99%
“…The development of a fatal immune complex-mediated glomerulonephritis (GN) 3 is closely associated with the appearance of elevated serum levels of IgG Abs with reactivities against nuclear Ags. Sera from these strains also contain Abs directed against endogenous retroviral envelope gp70 in the form of gp70-anti-gp70 immune complexes (gp70 IC) that appear with onset of the disease and increase throughout its course (2).…”
mentioning
confidence: 99%
“…Sera from these strains also contain Abs directed against endogenous retroviral envelope gp70 in the form of gp70-anti-gp70 immune complexes (gp70 IC) that appear with onset of the disease and increase throughout its course (2). In several genetic studies of murine lupus, levels of serum gp70 IC were shown to best correlate with development of severe GN (3)(4)(5)(6)(7)(8). Recently, the critical importance of gp70 IC formation in disease pathology was more directly demonstrated by induction of glomerular lesions and gp70 deposition in nonautoimmune mice after transfer of anti-gp70 mAbs derived from MRL-Fas lpr (9).…”
mentioning
confidence: 99%